Reflection for all healthcare staff: A national evaluation of Schwartz Rounds. Issue 1 (2nd January 2020) - Flanagan, Esther; Chadwick, Raymond; Goodrich, Joanna; Ford, Christy; Wickens, Rebecca
ABSTRACT: The emotional toll of working in healthcare is widely recognised, but staff rarely have time to reflect on their experiences. Schwartz Rounds provide an opportunity for all staff in a healthcare organisation to meet regularly and reflect on the human connections made with patients and the emotional impact of their work. They are now running in over 200 organisations across the UK & Ireland. In the first evaluation of a national sample in the UK, we review feedback received from a large sample of 402 Schwartz Rounds in a total of 47 organisations, including acute and non-acute NHS trusts and hospices. Analyses were undertaken to explore self-reported experiences of the Rounds, and differences between the proportions of professional staff groups attending. The overall experience of Schwartz Rounds was very positive across all settings. In particular, staff reported that Rounds helped them to gain insight into the working lives of their colleagues. There were no differences between the responses of clinical and non-clinical staff, indicating that all staff value a reflective space regardless of background. Healthcare staff value an opportunity to reflect on the emotional impact of their work. In increasingly overstretched and hurried services, it is a priority to provide this.